Waszyngton wobec francusko-brytyjskiego kompromisu morskiego 1928 r. - Żurawski vel Grajewski, Przemysław (Acta Universitatis Lodziensis. Folia Historica, 1997)
The collapse of the Three Powers Naval Conference in 1927 and the deadlock in the American-British negotiations in the 5th session of the Preparatory Commission for the Disarmament Conference constitucd the background of the U.S. attitude towards the so called Franco-British Naval Compromise of 1928. The agreement was a surprise for Washington who considered the Franco-British proposal offered to the United States to be an offensive one since it was based on the principles ignoring all the principal needs of the US Navy well know n to the British and the French since 1927. The Americans, unlike the Britons, beeing short of naval bases deployed in the world wide empire, needed large vessels having long radius of operation. Franco-British agreement put limitations exclusively on those clases of ships that were needed by the USA all the others leaving free of any limitation. This determined the American standpoint. Franco-British suggestion was rejected and the Congress passed new naval building program that however has never been put into force. Thus the diplomatic clash between Washington and London on naval superiority resulted in the deterioration of the American-British relations that in 1928 reached their lowest point in the whole interwar period.